The manufacturing sector and the future of Malaysia's economic development - Ha, Joon Chang (Penerbit Universiti Kebangsaan Malaysia, 2012)
This paper takes on the increasingly popular view that the service sertor should become Malaysia's new engine of growth, given the relative stagnation of its manufacturing sector in the last decade and the rise of post-industrial knowledge economy, in which the engines of growth consist of knowledge-intensive such as finance, engineering and design. This paper begin by explaning why the relative decline of manufacturing, or de-industrialisation . occurs and what kinds of negetive consequences it may have on a country's productivity growth and balance of payments.After this , the paper makes a number of points criticising the post-industrial knowledge economy discourse.First the knowledge economy is nothing new, as it was never the physical act of making things but the quality of the knowledge behind production that determind a country's economic success, even in the industrial era. Second,many knowledge intensive services look new only becouse they have been spun off or outsourced from the manufacturing firms that previously produced them. Third , we cannot separate the manufacturing sector from the knowledge sector as it is the key source of new productive knowledge, Fourth most service activities that have high rates of productivity are producer service for the manufacturing sector and can therefore be sustained without a successful manufacturing sector in the long run, Finally, the present article debunks some myths about the supposed service-based success stories od Switzerland, Singapore and (more recently) India.In the final section, the paper discusses the policy implications for Malaysia. While warning against making a fetish out of manufacturing, Malaysia needs to futher develop its national technological capabilities in manufacturing throught sustained investment in macninery, education training, and R&D supported by better policies regarding government procurement, social welfare, and other areas, in order to become a truly developed economy.